Perencanaan Dan Pembuatan Struktur Rangka Multicopter Dengan Konfigurasi Tiga Baling-Baling (Tricopter) - Alfakhri Biranda; Kaspul Anuar; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tricopter is one type of multicopter that has advantages in terms of total mass, volume and energy consumption. To make the Atha Mapper 2150 spacecraft capable of vertical take-off and landing, it is necessary to integrate the tricopter vehicle with the Atha Mapper 2150 vehicle. Therefore, in this study the tricopter frame structure is designed to be able to transport the Atha Mapper 2150 payload with MTOW less than 6 kg. The design process begins with the study of literature to understand the theories and concepts of material related to the research topic. Then determination of Design Requirement and Objective (DRO) based on the mission to make the Atha Mapper 2150 capable of taking off and landing vertically. The tricopter frame designed by Solidworks software. The frame of tricopter is made using Carbonfiber Reinforced Polymer (CFRP) on the arm and middle plate, acrylic for clamp and Polyactic Acid (PLA) for mounting motor. after the manufacturing is complete, the make measurement of the result of manufacture. the results obtained have a total mass of 686 grams with the outline dimensions in accordance with the requirements. Keywords : Tricopter, frame structure, MTOW, CFRP